Phylogenetic relationship and soil salinity shape intraspecific trait variability of Phragmites australis in the Yellow River Delta - Wu, Yiming; Liu, Lele; Yin, Meiqi; Guo, Weihua (Frontiers in Marine Science, 2022)
Soil salinization has been one of the main causes of ecosystem degradation in many estuarine wetlands under global climate changes, but it remains unclear how salinization shifts the phenotypic variability and genetic diversity of the foundation plant species in estuarine wetlands. To reveal the effects of salinization on natural populations of foundation plant species, we investigated the intraspecific variation of Phragmites australis using five functional traits (shoot height, leaf length, panicle length, seed number per panicle, and mass per seed) and ten microsatellite markers in the five sites across the Yellow River Delta. The salinity was indicated by electrical conductivity, and the reproductive strategy was estimated by the ratio of panicle length to shoot height. The linear models showed that the shoot height, leaf length, and panicle length had significantly negative correlations to soil salinity, while the mass per seed had a significantly positive correlation to soil salinity. However, there were no significant relationships between the seed number per panicle or reproductive ratio and soil salinity. The genetic diversity within populations was high in all sites (He > 0.5), but the genetic differentiation between populations was very weak (FST from 0.0074 to 0.0212), which suggested that there was a strong genetic flow among populations. Genetic structure analyses showed two phylogenetic groups of P. australis distributed in four of five surveyed sites across the Yellow River Delta. Our study also found significant phylogenetic signals in the leaf length and mass per seed, suggesting a substantial role of phylogenetic relationship (technically, neutral genetic relatedness) in intraspecific variation and salt adaptation of P. australis. Our study provides novel insight into the adaptative responses of the foundation plant species to soil salinization from individual traits to population genetics and offers significant implications for ecological restoration and adaptive management of saline lands in estuarine wetlands.